Experimental evaluation of an energy storage system for medium voltage distribution grids enabling solid‐state substation functionality. Issue 2 (9th March 2021) - Klumpner, Christian; Rashed, Mohamed; De, Dipankar; Patel, Chintan; Asher, Greg
Abstract: "Smart grids" is a new concept of managing the power transfer in modern grids that will rely not only on the on‐line processing of a variety of consumption and generation power data but will also need new hardware to facilitate a flexible and efficient conversion and storage of electrical power to maintain grid stability under fast changing operating conditions. This paper presents the results of the experimental evaluation of a 1.5MJ/25kW energy storage system connected directly to a medium voltage grid to provide fast and flexible grid control capabilities. The demonstrator consists of a supercapacitor stack connected to a low‐voltage DC bus via interleaved converters whilst connection to the medium voltage grid is done either via a low voltage inverter and step‐up 50Hz transformer or via a cascaded modular multilevel converter fed by dual active bridge converters isolated by medium frequency transformers. The experimental features demonstrated are fast power peak levelling, reactive current injection, grid fault ride through whilst maintaining a high round trip efficiency over a wide power range. The concept on which the demonstrator was designed facilitated the implementation of the solid‐state substation with integrated energy storage concept that can further increase flexibility and reliability of future grids.